Regulations, institutions and income smoothing by managing technical reserves: international evidence from the insurance industry - Chrysovalantis Gaganis; Iftekhar Hasan; Fotios Pasiouras (Bank of Finland, 2015)
This paper investigates the role of technical reserves in the income smoothing behavior of insurance companies. This is one of the first attempts in the literature to trace such relationship in the insurance industry, especially at a multi-country setting. The experience of 770 insurance firms operating in 87 countries over the period 2000-2009 reveals that there is a significant evidence of income smoothing. The paper also finds that institutional characteristics, e.g., the rule of law, common law legal origin, economic freedom, and regulations relating to technical provisions and supervisory power constrain income smoothing but other factors such as capital requirements, tax deductibility of provisions, auditing, and corporate governance do not have a significant effect.
URN:NBN:fi:bof-201508181354
Keywords: 330